The Medical Emergency Team in Italy: an overview of in-hospital emergencies response: An overview of in-hospital emergencies response - Galazzi, Alessandro; Bonasera Vincenti, Nicola Maria; Giusti, Gian Domenico; Brioni, Matteo; Adamini, Ileana; Laquintana, Dario; Ristagno, Giuseppe; Grasselli, Giacomo (Acta Biomedica Atenei Parmensis, 2020)
Background and aim: Medical Emergency Team (MET), implemented in many hospitals worldwide, aims to improve the safety of in-hospital patients whose condition is deteriorating. This study describes MET presence and organization in the Italian National Healthcare System Hospitals. Methods: A national survey with an online questionnaire was performed. The questionnaire, created ad hoc, was sent by e-mail to the nursing coordinators and MET referents of the Hospitals affiliated to the Italian National Healthcare System with an Anesthesia and Intensive Care service. Results: One hundred-ninety-seven hospitals were interviewed (36.2% of the whole national network). A dedicated MET, composed at least by an intensivist and a nurse, was present only in 118 cases (59.9%). The team was composed by a non-dedicated staff (67.8% of doctors, 69.5% of nurses) and a minimum shared standard of education for the nurse component was absent. One third of the estimated hospitals did not use a warning score for emergency call activation. Discussion and conclusion: This survey showed a heterogenous and often lacking organization of in-hospital emergency management in Italy. MET system needs to be implemented in terms of presence in the Italian hospitals, and standardized for personnel structure and training, and equipment availability. A broader study is necessary to compare our data with those of other European Countries to better identify the specific areas which need to be improved more promptly.